Comparison of the use of omega-3 fatty acids compound from New Zealand green lipped mussel and fish oil in the treatment of canine shoulder and coxofemoral osteoarthritis - Natwadee Mongkhon (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2012